FAKTOR-FAKTOR YANG MEMPENGARUHI PEMAKAIAN NAIL ART SEBAGAI FASHION STYLE BAGI MAHASISWA TATA RIAS UNESA - Agustina, Anisa; Sri Usodoningtyas; Biyan Yesi Wilujeng; Maspiyah (Program Studi Pendidikan Tata Rias, 2026)
Fashion today includes not only clothing and accessories but also functional items with futuristic and aesthetic designs that enhance personal appearance. One such element is Nail art, which has evolved into a form of lifestyle and self-expression, especially among young women. Among UNESA Cosmetology students, nail art is increasingly popular and serves as a means of personal identity. This study aims to explore the factors influencing the use of nail art as a Fashion choice among students. A qualitative approach was used through observation, interviews, and documentation. Data were analyzed using stages of data collection, reduction, presentation, and conclusion, with data validity ensured through source, technique, and time triangulation. The findings reveal that nail art is not solely driven by beauty trends, but also functions as a tool for expressing mood, identity, and personal values. The influencing factors are grouped into Fashion behavior, external factors, and internal factors, which are interrelated. Fashion behavior includes brand preferences, product knowledge, personal perception, and convenience—all of which significantly impact purchasing decisions. External factors involve trends, influencers, pricing, and digital media. Internal factors relate to emotions and self-expression through design aesthetics. In conclusion, nail art use among students is shaped by a combination of behavioral, external, and internal influences that reflect both Fashion sense and individuality. Keywords: Nail art, Fashion Style, Fashion Behavior, External Factors, Internal Factors